2017
DOI: 10.3389/fpls.2017.00966
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Cadmium Accumulation, Subcellular Distribution, and Physiological Responses to Understand Cadmium Tolerance in Apple Rootstocks

Abstract: Cadmium (Cd) is a nonessential and highly toxic element causing agricultural problems. However, little information is available about the variation in Cd tolerance among apple rootstocks and its underlying physiological regulation mechanisms. This study investigated Cd accumulation, subcellular distribution, and chemical forms as well as physiological changes among four apple rootstocks exposed to either 0 or 300 μM CdCl2. The results showed that variations in Cd tolerance existed among these rootstocks. Cd ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(45 citation statements)
references
References 77 publications
4
41
0
Order By: Relevance
“…Before harvest, gas exchange was measured for three mature leaves (leaf plastochron index range: 7-9) per plant in a CIRAS-2 photosynthesis system (PP Systems, Amesbury, MA, USA) as recommended by Zhou et al (2017).…”
Section: Gas Exchange Measurements and Plant Harvestmentioning
confidence: 99%
See 2 more Smart Citations
“…Before harvest, gas exchange was measured for three mature leaves (leaf plastochron index range: 7-9) per plant in a CIRAS-2 photosynthesis system (PP Systems, Amesbury, MA, USA) as recommended by Zhou et al (2017).…”
Section: Gas Exchange Measurements and Plant Harvestmentioning
confidence: 99%
“…These inconsistencies may be explained by the relative differences between herbaceous and woody plants in terms of Cd uptake and accumulation. In general, fruit trees have strong abilities to accumulate Cd in their roots and block its translocation to their aerial organs (Nada et al 2007, Zhou et al 2017). In the present study, melatonin-promoted HMA4…”
Section: Exogenous Melatonin Reduced Root CD Uptake and Translocationmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on metal-tolerant and metal-sensitive plant genotypes, ecotypes and species revealed that tolerant variants often exhibit constitutively higher antioxidant activity and accumulation of antioxidative compounds (Giannakoula et al 2010;Martins et al 2013;Zhou et al 2017;Muszyńska et al 2018b;Ferrer et al 2018). In D. jasminea treated with HM, irrespectively of treatment duration, antioxidant machinery was significantly reorganized.…”
Section: Major Players Of Heavy Metal Acclimation In D Jasmineamentioning
confidence: 99%
“…For instance, Cd is immobilised in the cell wall with pectate or sequestrated in vacuoles in undissolved forms, reducing Cd mobility and toxicity in apple rootstocks (Zhou et al . ). In Populus × canescens Cd is preferentially accumulated in the transport pathway accompanied by sulphur‐containing ligands, which can detoxify Cd (He et al .…”
Section: Introductionmentioning
confidence: 97%